Determinación de los contaminantes producto de la combustión del parque automotor a gasolina en la parroquia Eloy Alfaro, ciudad de Latacunga, período 2015 - Martínez Martínez, Jessica Lorena (2016)
The present investigation gives a new perspective on the atmospheric pollution generated by gasoline-based car fleet in the Eloy Alfaro Parish, it focuses on theoretical framework of environmental problems due to atmospheric pollution caused by the excessive increase of the automobile fleet, it mentions that motor vehicles and the products from its transformation into the atmosphere have become in important parts of any pollution problem. It Mentions the legislation applicable to the environment and the pollution by mobile sources and the permissible limits for gasoline vehicles. The results of monitoring about gases emitted by the vehicles was measure whith the AVL DITEST gases meter which determine the presence of carbon monoxide and non-burn hydrocarbons; the obtained data were proved with the Ecuadorian Technical Standard NTE INEN 2 204:2002, where the information of the analysis is elemental for generating a data base as fundamental tool for the establishment of strategies in order to reducie emissions, achieving the fulfillment of Transportation, Traffic and Road Security, law the maintenance of motor cars by their owners and the use of environmentally friendly ecological fuel.